Exploring the determinants of brown adipose tissue function in early life using infrared thermography - Robinson, Lindsay (2020)
There are significant gaps in our understanding of the developmental physiology of brown adipose tissue (BAT) between the neonatal period and adulthood. Studies of BAT in childhood are limited to the retrospective analysis of radiolabelled positron emission tomography (PET) imaging untaken for paediatric oncological diagnosis, treatment or monitoring. This thesis aimed to utilise supraclavicular skin temperature (TSCR), derived from infrared thermography (IRT), as a non-invasive, surrogate marker of BAT thermogenic function in children and, to use this methodology to identify determinants of BAT function in early life.